Analysis of a novel vertical axis twin-rotor wind turbine performance in an urban environment - Sachar , Shivangi; Doerffer , Piotr; Flaszyński , Paweł; Doerffer , Krzysztof; Grzelak , Joanna; Reiter , Andrzej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The study presented in this paper demonstrates the findings concerning a twin-rotor vertical-axis wind turbine patented by IMP PAN. Motivation for this wind turbine design was significantly driven by the need to exploit the wind energy available in an urban environment. The primary anticipated advantage is the substitution of the Savonius rotor by a new system allowing lighter and cheaper construction. The improvement of the wind turbine prototype presented took over three years, and the final modified version of the wind turbine underwent long-term testing. The paper presents a detailed description of the operational parameters and measured characteristics. One of the main objectives of the research was to test this novel wind turbine in a real environment, which is highly influenced by incoming wind conditions. The wind characteristics experienced by the turbine mounted on the roof of the IMP PAN building during the test period were demonstrated using Weibull distributions. Apart from wind conditions, the main goal of the measurements was to estimate the power characteristics of the novel wind turbine design. Measurements included output of the generator, consisting of voltage and current, the product of which allowed for determining the power extracted from the generator. Another important quantity was the speed of rotation of both turbines. The ratio of wind speed and the speed of rotation allowed for estimating the quality of the power extraction algorithm, which should be operated at TSR ≈ 1.0. The results obtained show that the power extraction algorithm could still be improved. The paper also contains an analysis of the dynamic effect of wind fluctuation on the rotor behavior, and the determination of the correlation of rotor response delay to wind gusts. The reduction of the wind velocity peak effect on energy production is discussed.